Synthesis of a Heavy-Atom-Free BODIPY and its Photooxygenation of 1-Naphthol to 1,4-Naphthoquinone - Zhou, Meizhu; Hu, Xinhu; Zhang, Dongxiang; Cui, Tianfang; Jiang, Xin-Dong (Synlett, 2023)
By using 1,5,6,7-dihydro-4H-indol-4-one, a carbonyl group was introduced onto a BODIPY photosensitizer. The resulting heavy-atom-free BODIPY is a highly effective producer of singlet oxygen with a calculated quantum yield (ΦΔ) of 0.68, compared with that of methylene blue (ΦΔ = 0.57). Photooxygenation of 1-naphthol to 1,4-naphthoquinone was achieved by using this heavy-atom-free BODIPY catalyst in the presence of white-light irradiation under air atmosphere. Our work demonstrated a practical example of the design of a heavy-atom-free BODIPY, capable of efficient singlet-oxygen generation, with a potential in photocatalysis.
Keywords: BODIPY dyes; organophotocatalysis; difluoroboradiazaindacene; photooxygenation; photocatalysts